Development of Mobile Learning Based on Android Using Smart Apps Creator in Informatics Lessons of Grade XI in MA Negeri 2 Samarinda - Nur Raudah Datun Nisa; Fahmi Romisa (Politeknik Pertanian Negeri Samarinda, 2025)
In the rapidly developing digital era, Indonesia has shown significant progress in the use of technology, including in the world of education. Technology is used to facilitate various learning activities, such as accessing information, supporting learning activities, and facilitating tasks by teachers. However, the application of technology in education still faces several challenges, such as the implementation of the Independent Curriculum and limited facilities and infrastructure. Therefore, this study aims to develop mobile learning media and then assess the feasibility of the product through assessments from material experts, media experts and responses from teachers and students. The method used in this study is R&D (Research and Development) with the 4D model (Define, Design, Development, and Disseminate). With the results of the mobile learning feasibility test by one material expert with an average score of 94% with the criteria